LIKUIDITAS, KREDIT MACET DAN KINERJA KEUANGAN BPRS DI INDONESIA - Sapto Bayu Aji (Universitas Riau Kepulauan, 2022)
This study aims to determine the effect of Liquidity and Bad Credit on Financial Performance in BPRS companies registered with the OJK for the 2016-2020 period. Liquidity is proxied by Cash Ratio (CR) and Bad Loans is proxied by Non-Performing Loan (NPL), while Financial Performance is proxied by Return On Equity (ROE), Financing to Deposit Ratio (FDR) and Minimum Capital Adequacy Requirement (KPMM).This research is a causative research. The population in this study are BPRS companies registered with the OJK with a total of 173 companies. The sample selection used a purposive sampling technique and the research sample obtained was 68 BPR Syariah. The data in this study are secondary data obtained from the Financial Services Authority (OJK) and the website official of the company concerned. The data analysis used was descriptive analysis followed by requirements testing including normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The statistical method used to analyze the data using multiple linear regression analysis.The results showed that the liquidity ratio (Cash Ratio) and Bad Credit (Non-Performing Loan) partially had no significant effect on the financial performance of Return On Equity (ROE), Financing to Deposit Ratio (FDR) and Minimum Capital Adequacy Requirement (KPMM), while ratio of Non-Performing Loans (NPL)at Sharia BPRs registered with the Financial Services Authority (OJK) in the 2016-2020 period.